1997
DOI: 10.2337/diacare.46.10.1601
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and Sulfonylurea Therapy in NIDDM Patients: Are the Effects on Lipoprotein Metabolism Different Even With Similar Blood Glucose Control?

Abstract: This study evaluates the effects of insulin versus glibenclamide on lipoprotein metabolism at comparable levels of blood glucose control, in particular on the concentration and distribution of VLDL subfractions and lipolytic enzyme activities in nine NIDDM men (aged 56 +/- 3 years, BMI 26.5 +/- 0.9 kg/m2) (means +/- SE) participating in a crossover study. After a 3-week washout period, patients were randomly assigned to 2-month treatment periods (insulin or glibenclamide); thereafter, each patient crossed to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 17 publications
3
23
1
Order By: Relevance
“…particles and a lowered activity of hepatic lipase during insulin treatment [15]. Although VLDL subfractions and hepatic lipase activity were not measured in our study, it seems reasonable that similar changes explain the differences we found in postprandial lipaemia between insulin aspart and repaglinide treatment as both repaglinide and sulphonylureas are considered to exclusively act as insulin secretagogues [44].…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…particles and a lowered activity of hepatic lipase during insulin treatment [15]. Although VLDL subfractions and hepatic lipase activity were not measured in our study, it seems reasonable that similar changes explain the differences we found in postprandial lipaemia between insulin aspart and repaglinide treatment as both repaglinide and sulphonylureas are considered to exclusively act as insulin secretagogues [44].…”
Section: Discussionmentioning
confidence: 45%
“…This goal was achieved as the 24-h blood glucose profiles obtained were similar and there was no significant difference in A1c. While a few studies have been performed comparing effects of insulin treatment with oral hypoglycaemic agents during similar glycaemic control [15,16], this is the first study comparing these rapid-acting treatments with main effects in the postprandial phase. We found differences in a number of variables including lipid metabolism and the IGF-system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insulin therapy or treatment with sulfonylurea type drugs (13) have differential effect on lipof,-otein metabolism at least in the NIDDM patients (14). In view of the above it was of interest to find out if the extent of glycosylation of erythrocyte membrane proteins and serum proteins, aswell asthe activities (DTNB) and vanadium ttee adenoine 5' ldplx~l~t~le, sodium salt (A'I'F)) were purchased from SRL, India.…”
Section: Introductionmentioning
confidence: 99%